Case report: A variant of the FIG4 gene with rapidly progressive amyotrophic lateral sclerosis - Yilihamu, Mubalake; Liu, Xiaolu; Liu, Xiaoxuan; Chen, Yong; Fan, Dongsheng (Frontiers in Neurology, 2022)
Heterozygous autosomal-dominant FIG4 mutations are associated with amyotrophic lateral sclerosis (ALS). Here, we describe a variant of the FIG4 gene (c.350dupC, p.Asp118GlyfsTer9) in a patient with rapidly progressive ALS that has not previously been reported in ALS or primary lateral sclerosis (PLS) patients before. Our study provides further information on the genotypes and phenotypes of patients with FIG4 mutations.